In vitro activity of apramycin against multidrug-, carbapenem- and aminoglycoside-resistant Enterobacteriaceae and Acinetobacter baumannii - Juhas, Mario; Widlake, Emma; Teo, Jeanette; Huseby, Douglas L; Tyrrell, Jonathan M; Polikanov, Yury S; Ercan, Onur; Petersson, Anna; Cao, Sha; Aboklaish, Ali F; Rominski, Anna; Crich, David; et al. (Journal of antimicrobial chemotherapy, 2019)
Abstract Objectives Widespread antimicrobial resistance often limits the availability of therapeutic options to only a few last-resort drugs that are themselves challenged by emerging resistance and adverse side effects. Apramycin, an aminoglycoside antibiotic, has a unique chemical structure that evades almost all resistance mechanisms including the RNA methyltransferases frequently encountered in carbapenemase-producing clinical isolates. This study evaluates the in vitro activity of apramycin against multidrug-, carbapenem- and aminoglycoside-resistant Enterobacteriaceae and Acinetobacter baumannii, and provides a rationale for its superior antibacterial activity in the presence of aminoglycoside resistance determinants. Methods A thorough antibacterial assessment of apramycin with 1232 clinical isolates from Europe, Asia, Africa and South America was performed by standard CLSI broth microdilution testing. WGS and susceptibility testing with an engineered panel of aminoglycoside resistance-conferring determinants were used to provide a mechanistic rationale for the breadth of apramycin activity. Results MIC distributions and MIC90 values demonstrated broad antibacterial activity of apramycin against Escherichia coli, Klebsiella pneumoniae, Enterobacter spp., Morganella morganii, Citrobacter freundii, Providencia spp., Proteus mirabilis, Serratia marcescens and A. baumannii. Genotypic analysis revealed the variety of aminoglycoside-modifying enzymes and rRNA methyltransferases that rendered a remarkable proportion of clinical isolates resistant to standard-of-care aminoglycosides, but not to apramycin. Screening a panel of engineered strains each with a single well-defined resistance mechanism further demonstrated a lack of cross-resistance to gentamicin, amikacin, tobramycin and plazomicin. Conclusions Its superior breadth of activity renders apramycin a promising drug candidate for the treatment of systemic Gram-negative infections that are resistant to treatment with other aminoglycoside antibiotics.